Analisis Pengaruh Pengendalian Internal, Sistem Informasi Akuntansi, Kesesuaian Kompensasi Terhadap Pencegahan Kecurangan Pada Dinas Pemberdayaan Masyarakat Desa, Kependudukan, Dan Pencatatan Sipil Provinsi Riau - Erma Nuril Fajriah; Nur Fitriana (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The purpose of this study was to determine the Effect of Compensation Suitability, Internal Control, Accounting Information Systems on Fraud Prevention at the Riau Province Village Community Empowerment, Population, and Civil Registration Office. The research method used a qualitative descriptive method using two data, namely primary data and secondary data. Primary data was obtained from interviews with informants, documentation during internships and observations. Secondary data was obtained from previous research results and books related to the research topic. The results showed that the Compensation Suitability Factor, Internal Control, Accounting Information Systems had a significant effect on fraud prevention at the Riau Province Village Community Empowerment, Population, and Civil Registration Office. However, financial education, morality, transportation and accountability factors are challenges for the Riau Province Village Community Empowerment, Population, and Civil Registration Office in increasing public knowledge in managing village cash. In the study, the researcher had limited time in the internship activities which were carried out in only two months so that it had an impact on the research results which were less comprehensive and obtained limited information. It is hoped that further researchers can conduct comprehensive research by highlighting broader factors so that better research results can be obtained.